Los hijos de Sánchez : autobiografía de una familia mexicana ; Una muerte en la familia Sánchez - Lewis, Oscar, 1914-1970 (Antropología (Fondo de Cultura Económica (Mexico)), 2012)
Studies a marginalized family in Mexico City during the 1950s. Jesús Sánchez and his four children live with economic problems and poor neighborhoods. The story continues in A death in the Sánchez family with the pain and difficulties of burying their dead with dignity.